Evaluación de las cinéticas de precipitación y estabilización de asfaltenos (2020)
"Heavy and extra-heavy crude oil transport requires the implementation of several treatments that reduce energetic requirements in pump stations. One of the most used is the dilution. Although its main objective is viscosity reduction, it generates compositional changes in crude oil that promote the asphaltene precipitation and can form deposits in pipes and decrease the flow capacity. To control these problems, chemical additives (dispersants and inhibitors) are injected. However, there is little knowledge of their action mechanism; as a result, laboratory tests are inefficient to determine their performance. In this work, the asphaltene precipitation and stabilization in two crude oil model systems were studied. It is based on kinetics monitoring of structural stability through transmission/backscattering measurements and morphological/topographic information using atomic force microscopy (AFM)." -- Tomado del formato de documento de grado